INSURANCE FOR THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN UZBEKISTAN: https://doi.org/10.5281/zenodo.13968375 - Otashev, Jahongir (International scientific and practical conference, 2024)
By 2030, Uzbekistan set an ambitious goal to become an upper-middle-income nation, putting special emphasis on developing a sizable and stable middle-class socioeconomic stratum. The present reforms in Uzbekistan predominantly target the development of small enterprises and private entrepreneurship (SME) as SMEs have the greatest potential for creating a true base for forming a middle class. In addition to outlining the evidence for the SME’s social and economic value, this article also addresses the current state of SME policy and its future prospects in Uzbekistan.